2022
DOI: 10.1186/s12944-022-01684-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cholesteryl ester transfer and phospholipid transfer proteins aggravated psoriasis in imiquimod-induced mouse models

Abstract: Background Psoriasis is a chronic inflammatory skin disorder related to dyslipidemia, with decreased high-density lipoprotein (HDL). Various cell types express phospholipid transfer protein (PLTP) as well as cholesteryl ester transfer protein (CETP). Their elevated levels among transgenic (Tg) mice led to reduced HDL and a higher risk of atherosclerosis (AS). This study examined whether elevated CETP and PLTP could aggravate psoriasis in a psoriasis vulgaris mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…CETP is a lipid transport protein in plasma that moves CEs from HDL to lipoproteins with apoB ( 151 ). CETP may have contradictory roles in inflammation.…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…CETP is a lipid transport protein in plasma that moves CEs from HDL to lipoproteins with apoB ( 151 ). CETP may have contradictory roles in inflammation.…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%
“…investigated the role of CETP in psoriasis. And the results showed that CETP-transgenic mice had significantly higher levels of IFN-γ, IL-1, IL-6, IL-17A, IL-17F, IL-22, and IL-23 in lesions and higher serum levels of TNF-α, IL-17, and IL-6 after IMQ-stimulation ( 151 ). The results of the study by Jun Chen et al.…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%